Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - 1.5 - Use of Properties - Problem Set 1.5 - Page 34: 71



Work Step by Step

We substitute $x=-2$ and $y=7$ in the given expression and evaluate it using order of operations (PEDMAS): $2(x+y)-3(x-y)$ =$2(-2+7)-3(-2-7)$ =$2(5)-3(-9)$ =$10+27$ =$37$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.